Evaluation of Edible Polymer Coatings Enriched with Grape Seed Extract on Chicken Meat Nuggets - Prathyusha, K.; Mallika, E. Naga; Rao, B. Eswara; Rao , T. Srinivas (Journal of Meat Science, 2016)
The study aims at the preservation of quality and extension of shelf life of chicken meat nuggets by formulating a novel coating material made of edible polymers. Edible polymer sodium alginate was used which was enriched with grape seed extract for the shelf life extension of the coated chicken meat nuggets. The quality of the nuggets was studied in terms of pH, Thiobarbituric acid value, Peroxide value, Total Plate Count, Water loss analysis and sensory evaluation at both refrigeration (4±1oC) and frozen storage (-18±1oC) temperatures. Results indicated that the polymer coatings extended the shelf life of the nuggets. Nuggets coated with grape seed extract incorporated coating solution had a lower TBARS values, peroxide values, total plate counts when compared to the nuggets coated with sodium alginate and the control group. Sensory attributes like color, flavor, tenderness, juiciness and overall acceptability also differed significantly (p
Keywords: Chicken nuggets; Grape seed extract; Edible coatings; Sodium alginate